The Impact of loneliness and romantic relationship status towards quality of life among adult single women in Indonesia: The Impact of loneliness and romantic relationship status towards quality of life among adult single women in Indonesia - Gazadinda, Rahmadianty; Pasaribu, Maria Mutiara Christina (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
A single or unmarried woman is often stigmatized to feel lonely. Due to the unmarried status, a single woman tends to be stereotyped having sort of difficulties and their quality of life is affected. Despite of being unmarried, a single woman has the opportunity to protect their quality of life. This study aims to identify the impact of loneliness and romatic relationship status to quality of life among adult single women in Indonesia. 200 single women aged between 28 to 40 years old are included in this study. This study found that there is a significant impact between loneliness and romantic relationship status to a subjective evaluation for quality of life F(3, 196) = 16.053; sig. 0.000; R Square=0.197). However, there is no interraction effect between the level of loneliness and romantic relationship status to all quality of life’s dimension F(3, 197) = 2.267, p = 0.063; Wilks’Lambda=0.96; Partial eta squared = 0.05). The study only found a significant contribution on level of loneliness towards those quality of life’s dimension. Keywords: Loneliness, quality of life, single, woman, romantic relationship status